Development of fuzzy expert system for customer and service advisor categorisation within contact centre environment. - Shah, Satya Ramesh; Roy, Rajkumar; Tiwari, Ashutosh (Cranfield University, 2004)
In this paper, we describe the research and development of a fuzzy expert system methodology for categorising customer and customer service advisor (CSA) within customer contact centre (CCC) environment. On the basis of data collected through case studies carried out within customer contact centre, two step clustering analysis within SPSS was used to derive the categories for customers and advisors based on demographic, experience, business value and behavioural attributes. The fuzzy expert system assigns a new customer or advisor to the pre-defined categories and provides the corresponding membership values given into the system using fuzzy logic. The author has explained the steps which were followed for the development of the fuzzy expert system. A prototype system has been designed and developed to identify the type of customer and CSA based on the demographic, experience and behavioural attributes. Experimental results are provided and the methodology is validated within the case study approach.
Keywords: Fuzzy Expert System; Customer and Advisor Categorisation; Soft Computing; Contact Centre